First report of Fusarium culmorum (W.G. Sm.) Sacc causing crown rot on wheat in Jordan - Alananbeh, Kholoud (Plant disease, 2023)
Fusarium crown rot (FCR) is a disease caused by numerous Fusarium species, primarily F. culmorum (W. G. Sm.) Sacc., F. pseudograminearum (O'Donnell & T. Aoki), and F. graminearum Schwabe (Paulitz et al., 200). FCR on wheat is a worldwide distributed disease that causes significant yield losses. In the Middle East, FCR was reported in Iraq (Motallebi et al., 2015; Matny et al., 2019) and Syria (Motallebi et al., 2015). In Jordan, Fusarium occurrence on wheat was documented in a checklist publication in 1984 (Mamluk et al., 1984) without further identification of the causative species and its pathogenicity level. There have been no other reports of Fusarium on wheat in Jordan since then. Symptoms of Fusarium crown rot were observed in 2016-2022 (Alananbeh et al., 2018) across Jordan through annual surveys of wheat diseases. The disease severity was higher in the dry seasons such as that of 2017 and 2021. Very severe symptoms were noted on wheat planted at the University of Jordan experimental wheat plots (n=4) in 2016-2022. A total of 40 symptomatic plants were randomly collected from these plots. Roots and stems of the 40 plants were then cut into small sections, disinfected in 0.5% hypochlorite for 5 minutes, 70% ethanol for one minute, and finally rinsed in sterile distilled water three times. The sections were dried under the laminar flow, plated on potato dextrose agar (PDA), and incubated for 10 -14 days at 25 ℃. The fungal cultures were purified by hyphal tipping. At least one pure isolate exhibited a typical morphology of F. culmorum was recovered from each plant. The colonies of pure cultures grew rapidly on PDA with fluffy floccose aerial mycelium and dark red to reddish brown pigment diffused in the agar. The isolates produced monophialidic conidiogenous cells. The formed marcoconidia were slightly curved, with pointed apical and foot cells, 3-5 septated, on average 28.5 - 46.5 X 4.5-7.0 μm, indication the cultures as Fusarium spp. (Figure 1). Chlamydospores were intercalary in hyphae and microconidia were absent. Two representative isolates (Iso-1 and Iso-2) identified putatively as F. culmorum, based on their morphological features, were sent to Macrogen Inc., South Korea to Sanger sequence a portion of the translation elongation factor 1-α gene using the EF1/EF2 primers (Geiser et al. 2004). Raw sequences were used to create consensus sequences using the BioEdit sequence alignment editor. The consensus sequences for the two representatives isolates were used to conduct BLASTn queries of NCBI (https://www.ncbi.nlm.nih.gov) which revealed they are 99.67% and 100% identical to MW233082.1, a TEF11-α sequence of the ex-epitype of F. culmorum (NRRL 25475, Crous et al. 2021). The two sequences generated herein were accessioned in GenBank (accession numbers: OQ785278 and OQ785279). Combined with the morphological and molecular analysis, the Iso-1 and Iso-2 were identified as Fusarium culmorum. The pathogenicity of the isolates was tested on two wheat cultivars using two methods: in vitro on seeds grown in sterile dishes and on seedlings. A 4 X 104 macroconidia suspension was prepared from 10 day-old culture of the isolate grown on PDA at 28 ºC. Seeds of two wheat cultivars, Hourani and Norsi were surface sterilized in 1% (v/v) bleach and rinsed in sterile distilled water three times. For the first method, seeds were soaked in the F. culmorum conidia suspension for 15 min and then dried using filter paper. The seeds were plated onto sterile paper towels in sterile plastic boxes and placed in a growth chamber. Three replicates with 10 seeds/replicate were used. Control Mock treatments used seeds treated with sterile distilled water. The germination percentage, coleoptile length, radicle length, longest seminal root length, and number of seminal roots were measured after 5 days. For the seedling-based pathogenicity test, seeds were planted in seedlings trays filled with sterilized 1:1:1 peat moss: sand: soil. 5 mL conidia suspension was drenched following seedling emergence. Ten replicates with one seed/replicate were used. Plants were watered when necessary to maintain appropriate soil growth conditions. The control seedlings were drenched with sterile distilled water. Disease symptoms were rated by the disease severity index (CRI) described by Mitter et al. (2006) after 35 days of inoculation. The in vitro test showed a reduction of germination and other seeds measurements in the presence of F. culmorum as compared to the control (Table 1 and Table 2, Figure 2). Similarly, the seedling's height, length of discoloration, disease score, disease severity index and germination percentage were all reduced in F. culmorum treated seedlings compared to the control. The two experiments showed that Cv. Norsi was more susceptible to FCR than Hourani (Table 1, Figure 2). F. culmorum was re-isolated from the roots of inoculated plants of both cultivars. The present study is the first report of the crown rot pathogen, F. culmorum on Jordanian wheat. Fusarium culmorum can cause significant economic losses and current research is ongoing to survey FCR-associated Fusarium spp. in Jordan, their genetic diversity, and QTL mapping for resistance genes in wheat landraces